Heading in soccer: More than a subconcussive event?. (28th February 2017) - Lingsma, Hester; Maas, Andrew
Abstract : Sports-related concussions are increasingly recognized as a public health problem, 1, 2 not only because of their immediate effects, but in particular because of reported associations with later cognitive decline. 3